Survival rates from a long-term (12-months) multiple driver aquarium experiment with the cold-water coral Desmophyllum pertusum - Beck, Kristina K; Roberts, J Murray; Burns, Zoe; Easton, Blair; Kaye, Sarah; Peña Fernández, Marta; Wolfram, Uwe; Hennige, Sebastian (PANGAEA, 2025)
We conducted a long-term (12 months) multiple driver aquarium experiment under future environmental conditions at St Abbs Marine Station (UK) with the cold-water coral Lophelia pertusa (syn. Desmophyllum pertusum) sampled from Tisler Reef (Skagerrak). The experiment consisted of four different treatments to investigate the combined effect of ocean acidification, warming, deoxygenation and food limitation on their physiology: 1) control (9 °C, pH 8.1, 100 % oxygen, 100 % food availability), 2) multiple stressor with high feeding (HF; 12 °C, pH 7.7, 90 % oxygen, 100 % food availability), 3) multiple stressor with low feeding (LF; 12 °C, pH 7.7, 90 % oxygen, 50 % food availability) and 4) reduced oxygen (9 °C, pH 8.1, 90 % oxygen, 100 % food availability). Every treatment consisted of three replicate tanks with four live corals (12 in total). Water parameters (temperature, salinity, pH and oxygen concentration) were measured five times per week in every coral tank. The survival rate of coral specimens was determined after 1.5, 3, 4.5, 6, 7.5, 9, 10.5 and 12 months of the experiment.
Keywords: calcification; climate change; Deoxygenation; Desmophyllum pertusum; energy reserves; food limitation; growth; Laboratory experiment; ocean acidification; Respiration; warming